Psychological distress, intimate partner violence and substance use in a representative sample from Mexico: A structural equation model - Ortega Ceballos, Paola Adanari; Rivera Rivera, Leonor; Reynales Shigematsu, Luz Myriam; Austria Corrales, Fernando; Toledano-Toledano, Filiberto; Pérez Amezcua, Berenice (Frontiers in Public Health, 2023)
Intimate Partner Violence (IPV) is a public health concern associated with multiple adverse health outcomes, including psychological distress (PD). Objective: To assess the association of IPV and psychological distress, and the mediation of tobacco and alcohol consumption in a national representative sample from Mexico. Material and methods: Data from the Encuesta Nacional de Consumo de Drogas, Tabaco y Alcohol (ENCODAT) were analyzed. The sample included 34,864 people between the ages of 12 and 65 with a partner. Using Structural Equation Modeling (SEM), the association between IPV, use alcohol, tobacco and psychological distress was measured. Results: The population was composed of women (51.9%) and men (48.1%); 15.1% (women=18.2% and men=11.9%) reported IPV in the last year. The prevalence of psychological distress in the last year was 3.3%, being 3.8% in women and 2.7% in men. Results from the SEM in women indicated a direct positive effect of the IPV construct on psychological distress (β= 0.298, p<0.01); these findings confirmed that IPV tended to systematically increase psychological distress. Likewise, the presence of IPV increased the consumption of tobacco (β= 0.077, p<0.01) and alcohol (β= 0.072, p<0.01). The SEM results in men showed that alcohol and tobacco consumption tended to increase in the presence of IPV (β= 0.121, p<0.01 and β= 0.086, p<0.01 respectively) and, in turn, alcohol consumption and tobacco tended to increase psychological distress (β= 0.024, p<0.01 and β= 0.025, p<0.01, respectively). Conclusion: This study indicated that in women, IPV had a direct effect on psychological distress and on alcohol and tobacco consumption. Meanwhile in men, alcohol and tobacco consumption had a mediating effect between IPV and psychological distress. The empirical findings of this study will contribute towards the design of public health policies for the prevention and attention of IPV, alcohol and tobacco consumption, and consequently address the mental health consequences derived from these problems.